DEVELOPMENT OF ANIMATED VIDEOS ON SUBSTANCE MATERIALS AND THEIR CHANGES USING PROBLEM BASED LEARNING TO INCREASE LEARNING MOTIVATION - Wirawati, Ni Putu Candra; Albaiti; Sahertian, Tony Natalian (Jurnal Ilmu Pendidikan Indonesia, 2026)
The purpose of the research is to find out (1) How to make an animated video; (2) Feasibility analysis of animated videos; (3) Animation video development; (4) Evaluation of increased learning motivation; and (5) Evaluation of improving learning outcomes. The research method is Research and Development (R&D) with the ADDIE procedural model. The research was conducted at SMP Negeri 1 Depapre with a total of 25 students. The results of the study showed that: The feasibility analysis of animated videos was obtained based on validator validation (93.69% of the category strongly agreed), peer feasibility test (94.15% of the category strongly agreed), and student trials (97.62% strongly agreed) so that the animated video was suitable for use; The development of animated videos is carried out by making visualizations of abstract concepts on substance materials and their changes so as to help students understand, using examples of solving everyday problems; The evaluation of increased learning motivation was obtained and there was an increase in motivation.